2021
DOI: 10.1038/s41393-021-00708-3
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and mental health in individuals with spinal cord injury during the COVID-19 pandemic

Abstract: Study design Cross-sectional, observational study. Objectives To understand how resilience, access to personal care attendants (PCAs) and medical supplies, and concerns about medical rationing, finances, and social isolation are related to overall and mental health in individuals with spinal cord injury (SCI) in the context of the COVID-19 pandemic. Setting Community dwelling adults ( N = 187) with SCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Our findings are similar to other research, including a study showing that individuals with SCI reported that the COVID-19 pandemic had a negative impact on their mental and social health, in particular that their feelings of social isolation increased (Monden et al, 2021). In another SCI cohort, feelings of social isolation were associated with a greater perceived impact of the COVID-19 pandemic on mental health and overall health (Mikolajczyk et al, 2021). Our study showed that the COVID-19 pandemic triggered several emotions in veterans with SCI, such as worry, fear, doubt, lack of motivation, and feelings of social isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are similar to other research, including a study showing that individuals with SCI reported that the COVID-19 pandemic had a negative impact on their mental and social health, in particular that their feelings of social isolation increased (Monden et al, 2021). In another SCI cohort, feelings of social isolation were associated with a greater perceived impact of the COVID-19 pandemic on mental health and overall health (Mikolajczyk et al, 2021). Our study showed that the COVID-19 pandemic triggered several emotions in veterans with SCI, such as worry, fear, doubt, lack of motivation, and feelings of social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Other survey studies (mostly online, one by telephone) reported that individuals with SCI experienced anxiety (Gustafson et al, 2021; Hearn et al, 2021; Vives Alvarado et al, 2021) and depression (García-Rudolph et al, 2021; Gustafson et al, 2021; Vives Alvarado et al, 2021) during the pandemic. In addition, individuals with SCI were at risk of feeling socially isolated in response to the pandemic (Hearn et al, 2021; Mikolajczyk et al, 2021; Monden et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the psychosocial domain, lost access to personal supports such as family, personal networks, and formal support workers increased social isolation and complicated access to healthcare information [4-7, 13, 14]. Lower resilience and quality of life have also been reported, with increased depression and anxiety, particularly around accessing services [6,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the small existing literature on the direct and indirect effects of the COVID-19 pandemic on the at-risk and marginalized SCI population are cause for significant concern, indicating a pressing need for additional investigations on the adverse impacts of the pandemic and the potential risk and protective factors predicting those impacts. Many of the studies in the current literature include samples that are severely restricted in terms of sex (Vives Alvarado et al, 2022), race (Hearn et al, 2022; Mikolajczyk et al, 2021; Monden et al, 2021), and/or age (Matsuoka & Sumida, 2022). Studies with greater diversity in sample characteristics are needed to more thoroughly examine predictors of pandemic impacts.…”
mentioning
confidence: 99%
“…The researchers reported a significant increase in symptoms of depression and a significant decrease in resilience and linked those changes to difficulties accessing healthcare resources and goods. In a relatively large survey of 187 people with SCI (Mikolajczyk et al, 2021), researchers reported that having an incomplete injury, concerns about medical rationing, disrupted medical supplies, and social isolation predicted a self-reported negative impact of the pandemic on overall health. Perceived mental health impacts were associated with younger age, medical rationing concerns, less resilience, and social isolation.…”
mentioning
confidence: 99%